Relation of Immediate Postnatal Growth With Obesity and Related Metabolic Risk Factors in Adulthood: The Northern Finland Birth Cohort 1966 Study - Tzoulaki, Ioanna; Sovio, Ulla; Pillas, Demetris; Hartikainen, Anna-Liisa; Pouta, Anneli; Laitinen, Jaana; Tammelin, Tuija H.; Jarvelin, Marjo-Riitta; Elliott, Paul (American Journal of Epidemiology, 2010)
The authors examined associations between postnatal growth velocity through age 2 years and metabolic outcomes at age 31 years in a population-based birth-cohort study of 3,778 Finns (1966–1998). Approximately 8 height measurements and 9 weight measurements were obtained from birth to age 2 years. Peak height velocity (PHV) and peak weight velocity (PWV) in infancy were derived from parametric growth curves fitted to longitudinal height and weight growth data. Body mass index (BMI), waist circumference (WC), high density lipoprotein (HDL) cholesterol, triglycerides, glucose, systolic and diastolic blood pressure (BP), and the metabolic syndrome were measured at age 31 years. PHV was significantly positively associated with systolic and diastolic BP and WC in adulthood. For each 8-cm/year (2-standard-deviation) increase in PHV, WC increased by 1.60 cm (95% confidence interval: 0.73, 2.46), after adjustment for potential confounders, including birth weight. PWV was significantly associated with adulthood systolic BP, WC, and BMI. A 4-kg/year higher PWV was associated with a 1.87-cm (95% confidence interval: 1.08, 2.65) larger WC in adulthood, after adjustment for potential confounders. HDL cholesterol (direct), triglycerides (inverse), and metabolic syndrome (inverse) displayed associations with PWV only after BMI was accounted for. These results showed that growth during the immediate postnatal period is associated with adulthood obesity and BP. Lifestyle changes from early life might be important in reducing adulthood obesity and high-BP risk.